2011 IEEE Global Engineering Education Conference (EDUCON) 2011
DOI: 10.1109/educon.2011.5773183
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the quality of social media in an educational context

Abstract: Social media enhanced learning systems bring new challenges to evaluate learning environments. Many features are common with any websites and can be evaluated with common criteria. But with social media users can also contribute content, change opinions and create communities for different needs, which bring new dimensions to a quality evaluation. This research focused on finding out which are the most important characters and functions in social media enhanced learning system in the context of higher educatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 7 publications
0
20
0
1
Order By: Relevance
“…The teachers perceived that web resources have the potential to capture students' interests to be active in the learning process, because the students preferred such resources and were keen users. Several researchers (Abrizah & Zainab, 2011;Afshari et al, 2009;Bland et al, 1979;Kay et al, 2009;Light & Polin, 2010;Recker et al, 2004;Silius et al, 2011;Wu et al, 2005) have confirmed that using digital resources provided an opportunity to engage students with the learning process and establish an effective student-centered teaching-learning environment.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…The teachers perceived that web resources have the potential to capture students' interests to be active in the learning process, because the students preferred such resources and were keen users. Several researchers (Abrizah & Zainab, 2011;Afshari et al, 2009;Bland et al, 1979;Kay et al, 2009;Light & Polin, 2010;Recker et al, 2004;Silius et al, 2011;Wu et al, 2005) have confirmed that using digital resources provided an opportunity to engage students with the learning process and establish an effective student-centered teaching-learning environment.…”
Section: Discussionmentioning
confidence: 81%
“…Similar to the teachers who participated in the current study, the teacher participants of previous studies (Light & Polin, 2010;Silius et al, 2011) also believed that using web resources allow them to feel more connected to their students and provide a new way of engaging them in classroom learning.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Social media services can be broadly divided into six categories: content creation and publishing, content sharing, social networking sites, collaborative productions, virtual worlds, and add-ons (Silius, Kailanto, & Tervakari, 2011). Popular Web sites like Facebook, Twitter, LinkedIn, YouTube, and so on certainly fall within this definition, and many university courses utilize such commercially available services.…”
Section: Introduction and Rationalementioning
confidence: 99%
“…Learning environments should also be "pedagogically usable" and support the different types of learners by providing various learning contexts according to selected pedagogical objectives [1] [2]. 1 WeSQu is available at http://iislab.ee.tut.fi/wesqu II.…”
Section: Introductionmentioning
confidence: 99%